Antibiotic prophylaxis with piperacillin–tazobactam reduces organ/space surgical site infection after pancreaticoduodenectomy: a retrospective and propensity score-matched analysis - Yifei Yang; Jianjie Sheng; Zhenghua Cai; Linxi Zhu; Chenglin Lu; Liang Mao; Yudong Qiu; Xu Fu (BMC Cancer, 2024)
Abstract Background The occurrence of surgical site infection (SSI) after pancreaticoduodenectomy (PD) is still relatively high. The aim of this retrospective study is to evaluate the efficacy of piperacillin-tazobactam as perioperative prophylactic antibiotic on organ/space SSI for patients underwent PD. Methods Four hundred seven consecutive patients who underwent PD between January 2018 and December 2022 were enrolled and analyzed retrospectively. The univariate and multivariate analysis were used to identify independent risk factors of organ/space SSI. Postoperative complications were compared between the two groups according to the use of prophylactic antibiotics by a ratio of 1:1 propensity score-matched (PSM) analysis. Results Based on perioperative prophylactic antibiotic use, all 407 patients were divided into the ceftriaxone group (n = 192, 47.2%) and piperacillin–tazobactam group (n = 215, 52.8%). The rate of organ/space SSI was 31.2% with the choice of perioperative antibiotics (OR = 2.837, 95%CI = 1.802–4.465, P < 0.01) as one of independent risk factors. After PSM, there were similar baseline characteristics among the groups. Meanwhile, the piperacillin–tazobactam group had a significant lower rate of organ/space SSI compared to the ceftriaxone group both before and after PSM(P < 0.05). Conclusions The adoption of piperacillin–tazobactam as perioperative prophylaxis for patients underwent PD reduced organ/space SSI significantly.